Directive emission from polymeric fluorophore with epsilon-near-zero squaraine molecular film - Choi Kyu-Ri; Kim Minjae; Wu Jeong Weon; D’Aléo Anthony; Lee Yeon Ui (Nanophotonics)
Enhanced directionality of photoluminescence emission has attracted attention due to its diverse application areas ranging from single-photon sources to fluorescence sensing and bio-imaging. Utilization of null phase advance in epsilon-near-zero (ENZ) medium is an important scheme to achieve the directive emission. Despite various designs proposed for ENZ-based directive emission, most of the ENZ mediums are restricted to subwavelength structures of metallic plasmonics or inorganic dielectrics. Here, we introduce an organic ENZ film placed on top of a polymeric fluorophore film to demonstrate a directive emission. By taking advantage of the structural coherence in the P3HT film and the ENZ response in the squaraine molecular film, 42 % increase in directive emission is achieved. Capability to control directive emission with organic ENZ films is highly useful in applications requiring bio-compatibility of a fluorophore-embedding medium.